Индуктивно-оптический преобразователь измерителя эксцентричности электрического кабеля - Гольдштейн А. Е. Александр Ефремович; Редько В. В. Виталий Владимирович; Фёдоров Е. М. Евгений Михайлович
опубл. 27.06.11, Бюл. № 18